2013
DOI: 10.2355/isijinternational.53.900
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transformation Behavior of a Deformed High Carbon Steel at Temperatures Above the Ae3

Abstract: The dynamic transformation behavior of deformed austenite was studied in a 0.79%C high carbon steel over the temperature range 743-823°C. The experiments were carried out in torsion under an atmosphere of argon and 5% H2. All these temperatures are above the orthoequilibrium Ae3 temperature of the steel. Strains of 0.25-4 were applied at a strain rate of 4 s -1 . The experimental parameters were varied in order to determine the effects of strain and temperature on the formation of strain-induced ferrite and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
(36 reference statements)
4
25
1
Order By: Relevance
“…4), in which it is shown that C is only rejected during plate formation when the C level exceeds about 0.1%. Transmission electron microscopy 5) and atom probe tomography 15) revealed the presence of fine carbides on dislocations and at grain boundaries; however, due to their fine scale they could not be detected using the EBSD techniques employed in the present work.…”
Section: Microstructurementioning
confidence: 39%
See 1 more Smart Citation
“…4), in which it is shown that C is only rejected during plate formation when the C level exceeds about 0.1%. Transmission electron microscopy 5) and atom probe tomography 15) revealed the presence of fine carbides on dislocations and at grain boundaries; however, due to their fine scale they could not be detected using the EBSD techniques employed in the present work.…”
Section: Microstructurementioning
confidence: 39%
“…After the second deformation, the samples were quenched in about 1 s, which has been shown to be rapid enough to prevent the static formation of polygonal ferrite and pearlite on cooling. 15) Further details of the experimental procedure as well as the flow behavior are available elsewhere. 10,11,16) …”
Section: Torsion Testingmentioning
confidence: 99%
“…24) These microstructures are similar to those that have been reported in other steels when dynamic transformation is taking place. 25,26) The presence of DT ferrite in the present samples was confirmed using EBSD techniques of phase identification. This is illustrated here in Fig.…”
Section: Sem and Ebsd Analysismentioning
confidence: 76%
“…The former forms displacively as a result of deformation in elapsed times of less than a millisecond. 8,14) The latter forms during cooling below the Ae 3 and requires times of 8 to 10 s in order to permit the partitioning of Mn and Si between the γ and α phases, respectively. 8,15) Accordingly, quench times of 1 to 2 seconds were employed, which correspond to cooling rates of about 500°C/s.…”
Section: Torsion Testsmentioning
confidence: 99%